Elementary School Teachers' Perceptions of Augmented Reality Learning Media through Assemblr Edu - Rizka Ummu Khoeriyah; Acih Trisnawati; Titin Sutinah; Imas Mulyati; Sri Mulyani; Devi Raswati; Maman Suryaman (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The development of digital technology has brought significant changes in education, particularly in how teachers teach and students learn. One innovation increasingly applied is Augmented Reality (AR) technology through the Assemblr Edu platform. This study aims to analyze elementary school teachers’ perceptions of using AR-based learning media via Assemblr Edu and to identify supporting and inhibiting factors in its implementation. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving eight elementary school teachers in Karawang Regency who participated in Assemblr Edu training. The results show that 75% of teachers perceived AR media as very effective in increasing students’ motivation and facilitating understanding of abstract concepts, especially in science and mathematics lessons. Teachers stated that the 3D visualization features enhanced student engagement and comprehension. However, limited infrastructure, especially unstable internet access in schools located in the outskirts of Karawang, remains a key barrier. Teachers emphasized the need for continuous mentoring and hands-on workshops to strengthen their ability to create AR-based learning materials. The findings highlight Assemblr Edu's potential as an innovative medium that supports teacher professionalism and digital literacy. These results can serve as a basis for regional policies on teacher-training programs that integrate AR technology into elementary education. Keywords: augmented reality, teacher perception, learning media, teacher professional development